Recovery of image data from flash memory - Muhammad Syamil Rafizain (Nanyang Technological University, 2021)
File data is not immediately removed from a flash memory. Therefore, it is possible to recover deleted files whose file contents have not yet been erased. Deleted files are found in unallocated space, and to recover a deleted file, the unused space will be examined for any file data remnants that can be extracted.When an image is corrupted, some data inside the image file is either missing or overwritten. It is impossible to restore data corruption in this manner, and a corrupted image cannot be reconstructed without the aid of other files.We would like to recover JPEG images from the flash memory of an Android device. The efficiency of two different software will be compared in how well they can extract file data. A corrupted JPEG image will be extracted and reconstruction will be attempted to restore the corrupted image using its thumbnail.